Pengaruh Indeks Pembangunan Manusia Dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan Di Provinsi Lampung Pada Priode 2012-2023 - Bintang Shavira Zahra; Renita Dafa Arta Mevia; Rizki Aria Sona; Misfi Laili Rohmi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
All people certainly really want a peaceful and prosperous life, but in reality it is not that easy to get a decent life, there are many factors that become challenges such as the low human development index, very high unemployment rates and the problem of poverty which has mushroomed in various regions. . Poverty is also described as the most complex social problem so it must always receive special attention from the government. This study uses quantitative methods and uses secondary data obtained from the Lampung Province Central Statistics Agency, using data from 2012-2023. The aim of this research is to determine the influence of the Human Development Index and the open unemployment rate on the percentage of poverty in Lampung Province. The results of the multiple linear regression analysis test show that HDI and TPT simultaneously have a significant influence on the percentage of poor people. Likewise, partially HDI has a significant influence on poverty, while TPT has no significant influence on poverty in Lampung Province in the 2012-2023 period.